The Spitfire Story - Price, Alfred (London Arms and Armour Press, 1992)
This is an account of the conception, evolution and fighting record of the Spitfire.
Include Index and Illustration
Keywords: Spitfire (Fighter plane) -- World War (1914-1918) -- Military operations, Aerial--British